Phosphoinositides in the kidney - Leopoldo Staiano; Maria Antonietta De Matteis (Journal of Lipid Research, 2019)
Phosphoinositides (PIs) play pivotal roles in the regulation of many biological processes. The quality and quantity of PIs is regulated in time and space by the activity of PI kinases and PI phosphatases. The number of PI-metabolizing enzymes exceeds the number of PIs with, in many cases, more than one enzyme controlling the same biochemical step. This would suggest that the PI system has an intrinsic ability to buffer and compensate for the absence of a specific enzymatic activity. However, there are several examples of severe inherited human diseases caused by mutations in one of the PI enzymes, although other enzymes with the same activity are fully functional. The kidney depends strictly on PIs for physiological processes, such as cell polarization, filtration, solute reabsorption, and signal transduction. Indeed, alteration of the PI system in the kidney very often results in pathological conditions, both inherited and acquired. Most of the knowledge of the roles that PIs play in the kidney comes from the study of KO animal models for genes encoding PI enzymes and from the study of human genetic diseases, such as Lowe syndrome/Dent disease 2 and Joubert syndrome, caused by mutations in the genes encoding the PI phosphatases, OCRL and INPP5E, respectively.